2021
DOI: 10.1108/oir-01-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Bibi and Mr. Prime Minister: do different Facebook identities imply different messages for political leaders?

Abstract: PurposeSocial media has been widely adopted by politicians and political parties during elections and routine times and has been discussed before. However, research in the field has so far not addressed how a political leader's private or official social media account affects their message, language and style. The current study examined how Israeli Prime Minister Benjamin Netanyahu uses his private Facebook account, compared to his use of his official Facebook page “Prime Minister of Israel.”Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Next, since as our study was conducted on Facebook it is important to examine the unique traits of the platform in order to explain our findings. First, based on studies which identified that Facebook campaigning tends to be personal (Yavetz, 2021), populist (Ernst et al, 2019) and emotional (Bronstein, 2013), which characterizes women's style discourse on Facebook OIR 47,6 (Brandtzaeg, 2017), it is possible that these elements give women politicians a unique advantage on Facebook during campaigning. Second, our findings show that female politicians tended to post more about subjects such as welfare as opposed to male politicians (Table 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, since as our study was conducted on Facebook it is important to examine the unique traits of the platform in order to explain our findings. First, based on studies which identified that Facebook campaigning tends to be personal (Yavetz, 2021), populist (Ernst et al, 2019) and emotional (Bronstein, 2013), which characterizes women's style discourse on Facebook OIR 47,6 (Brandtzaeg, 2017), it is possible that these elements give women politicians a unique advantage on Facebook during campaigning. Second, our findings show that female politicians tended to post more about subjects such as welfare as opposed to male politicians (Table 8).…”
Section: Discussionmentioning
confidence: 99%
“…Since the move is in fact part of a wider trend of the personalization of election campaigns (Metz et al ., 2020), where the private life of the politician and their personality takes center stage, the nature of campaigning has become more intimate and personal. To illustrate, Yavetz (2021) found that Israel's PM Netanyahu uses his personal Facebook account (in parallel to his official “Prime Minister of Israel” Facebook page) to respond to events related to his family life with the aim of increasing sympathy towards him. In the same spirit, the nature of social media campaigning is more populist and emotional than traditional campaigning as several analyses showed that during social media campaigns, politicians tend to focus on emotional appeals in order to increase “fandom” and minimize dissent (Bronstein, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of digital media to communicate and transfer government information to citizens was significantly high during the Coronavirus outbreak days compared to routine times [ 3 , 59 ]. However, as can be seen in previous studies, various government organizations in Israel have already established the use of new digital platforms in order to disseminate information [ [60] , [61] , [62] , [63] , [64] ]. Regardless of the Coronavirus crisis, in recent years, many government organizations in Israel have adopted the use of social networks for the purpose of disseminating information to citizens and have also implemented many practices designed to increase engagement through the use of visual content (videos/photos), and up-to-date information about policy and operations [ 65 , 66 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As of January 2015, 108 out of 120 MPs were active on Facebook in varying scopes and frequencies (Mann and Lev-On, 2016). Some leading Israeli political figures maintain both personal and formal Facebook pages that enable them to maintain parallel and distinguished communication channels with their followers (Yavetz, 2022).…”
Section: Israel As a Case Study Of Vibrant Political Social Media Spherementioning
confidence: 99%